Penyuluhan Manfaat Umbi Lokal Canna Edulis Kerr di Masyarakat - Ferika Indrasari; Metrikana Novembrina; Rizky Ardian Hartanto Sawal (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Dependence on rice and wheat can be maintained or reduced by increasing the diet through changing the image of tubers such as the local tuber Canna Edulis Kerr. The purpose of service is to improve food security in the community. The method of implementing the activity is counseling using power point media. The results of the activity went well from licensing to the end of the activity. Conclusion Participants get direct benefits related to counseling the benefits of local tuber Canna edulis kerr in the community.